Meningkatkan Ketrampilan Menulis Paragraf pada Siswa Sekolah Dasar melalui Pembelajaran yang Menyenangkan - Avivvah Sulistyowati; Gressia Fani Ekawati; Luki Eka Ferdian; Miftahul Jannah; Bayu Purbha Sakti (CV. ITTC INDONESIA, 2025)
This study aims to improve elementary school students' paragraph writing skills through the application of the Pair Check cooperative learning model supported by YouTube media, images, and picture cards. Paragraph writing skills are an important aspect in learning Indonesian, but students often have difficulty in developing ideas coherently and interestingly. This study uses a Classroom Action Approach (CAR) which is implemented in two cycles, with elementary school students as research subjects. Data were collected through observation, written tests, and documentation. The results of the study indicate that the application of the Pair Check model facilitates cooperation between students and facilitates the process of correcting each other's work results. The use of YouTube media provides concrete examples of paragraph structure, while images and picture cards help students develop ideas visually and contextually. There was a significant increase in the quality and number of paragraphs written by students in each cycle. Thus, this learning strategy has proven effective in improving elementary school students' paragraph writing skills.